Academic databases in humanities and social sciences setting - Faletar Tanacković, Sanjica (Knjižnica, 2018)
Purpose: The study investigated perceptions and experiences of students at Faculty of Humanities and Social Sciences in Osijek, Croatia with academic databases. Methodology: The mixed-method study (self-administered print survey and semi-structured interviews) was conducted from October 2016 through February 2017. Quantitative analysis was conducted on 381 correctly completed questionnaires using the SPSS statistical package. Besides descriptive statistics, Chi-Square tests, T-tests, ANOVA, Mann-Whitney and Kruskal Wallis tests were used to test possible differences between the groups in the sample. Statistical difference was tested at the level of 95%. Results: Although 82.2% of respondents think that information literacy (IL) skills are important for their academic success, only 63% reported that they received some formal IL training at university level. The respondents self-assessed their Google searching skills with higher grades (Mean 4.31) than their academic database searching skills (Mean 3.69), and they reported a more frequent use of Google (53.8%) than databases (25.1%) for academic purposes. When asked about problems related to database searching, students reported several challenges: their systematic habit of using Google (48%), limited access to databases from home (42.3%), the (foreign) language of scholarly articles (35.2%) and their lack of searching skills (35.2%). In general, the findings suggest that humanities students receive less IL formal training at university level, they are to a lesser degree motivated (both externally and internally) to use academic databases and are more often inclined to use Google for academic purposes than social sciences students. In addition, findings suggest that there is a disciplinary difference regarding the perception of databases. Research limitation: Geographical limitations and small sample size. Originality/Practical implication: The results can influence the design of information literacy programs and library reference services.
Keywords: Hrvaška; informacijska pismenost; podatkovne zbirke; raziskave; študenti; visoko šolstvo